ADDRESSING INTERGENERATIONAL COLLABORATION CHALLENGES: CREATIVE SOLUTIONS IN COMMUNITY-BASED MOSQUE MANAGEMENT - Anissa Listianti; Ahmad Asrof Fitri; Sobirin Sobirin; Eka Zuni Lusi Astuti (Program Studi Manajemen Dakwah, FUAD, IAIN Pontianak, 2024)
In Curug Subdistrict, Tangerang Regency, particularly in Binong Village, there is a mosque with adequate facilities that still requires progressive programs to enhance community engagement and increase the vibrancy of Masjid Nurul Iman. The objective of this study is to understand the role and functions of idarah (administration) and imarah (prosperity) carried out at Masjid Nurul Iman, as well as its supporting and inhibiting factors. The population of this study consists of 165 people, with a sample of 10 respondents, including 4 mosque administrators and 6 congregants and community members. The research method is descriptive qualitative, with data collection techniques using interviews, observations, and documentation. The findings show that activities such as Majelis Taklim, which includes routine recitations for children, women, and men, charity for orphans and the underprivileged conducted twice a year (during Eid al-Fitr and Eid al-Adha), the formation of the Qurban committee, mosque renovations, and the celebration of Islamic holidays and tabligh akbar (grand sermons) are all community-involved activities. Additionally, the study found that supporting factors for the mosque's role in fostering community solidarity include good relationships between mosque administrators and the community, adequate facilities, the regular study circles organized by mosque administrators, and high community participation in mosque programs. On the other hand, the inhibiting factors include the lack of cooperation between mosque administrators and the younger generation, as well as the somewhat monotonous activities offered by Masjid Nurul Iman. This study highlights the mosque’s important role in community engagement and offers insights into potential improvements in program variety and youth involvement.